GC for flavonoids analysis: Past, current, and prospective trends. Issue 1 (15th December 2012) - Nolvachai, Yada; Marriott, Philip J.; Svec, Frantisek
<x xml:space="preserve">Abstract</x> Flavonoids represent one of the more abundant classes of phytochemicals. They are renowned for their health benefits against age‐related ailments and diseases. Several chromatography techniques have underpinned many chemical analysis methods, developed for superior flavonoid separation and identification. Among these, GC is one of the most powerful tools in separation science, providing precise measurement of a wide range of flavonoids. Combined with various detectors – most commonly MS–GC offers a sensitive and accurate tool for quantitative and qualitative flavonoids analysis. This review features developments in the application of GC and MS for flavonoids determination during past decades, progressing to recent developments and considering future trends. The review will highlight the state‐of‐the‐art of GC, with opportunities for multidimensional GC analysis also briefly discussed.